EMPLOYEES' ORGANIZATIONAL COMMITMENT: A STUDY OF THE EFFECTS OF PERFORMANCE ASSESSMENT, CAREER PLANNING, AND BANKING EMPLOYEE PARTICIPATIONS - Gadzali, Silvy Sondari (CENTRAL ASIA AND THE CAUCASUS, 2022)
Many empiric types of research have been conducted on the antecedents of employee organizational commitment. However, there is still little research that examines the effect of HR management praxis such as performance appraisal systems, career planning systems, and employee participation on organizational commitment. In this study, the effect of these three variables was tested in explaining employee work commitments in the banking sector in West Java. Based on a survey of 98 employees in 20 private banks in West Java, this study uses regression analysis, correlation analysis, and G-test to test hypotheses. The results showed that the performance appraisal system, career planning system and employee participation significantly influence employee work commitment. This result also indicates that employees' level of organizational commitment in the private banking sector in West Java is low. Therefore, this study suggests that for employees to be truly committed to their work, companies must make objective efforts to manage performance appraisals, career planning, and employee participation to ensure effective implementation and achieve expected results.